The Role of Penghulu in Harmonising the Marriage Age Limit Perspective of Imam As-Syatibi's Theory - Fathurrahman, Fathurrahman; Zaelani, Abdul Qodir; Syukur, Iskandar (Nurani, 2023)
The regulation of marriage age limit is contained in Law Number 16 of 2019 concerning Amendments to Law Number 1 of 1974 concerning Marriage, which is equalised to 19 years for men and women from the previous 19 years for men and 16 years for women. The Office of Religious Affairs as a government institution in charge and administratively responsible for the implementation of legal and recorded marriages is faced with the large number of early marriages recorded with Religious Court dispensation. This study aims to analyse the role of the headman in harmonising the age limit demanded by the law and the implementation of early marriage applications by the KUA in the maqāsid syarῑ'ah study of Imam As-Syatibi. This research is field research with qualitative descriptive method. Data were collected through interviews, documentation, and observation at 15 KUA sub-districts in West Lampung. The role of the penghulu in harmonising the demands of regulations and the implementation of early marriage, through three different patterns in the implementation of marriage and its recording. The first pattern is that the marriage is carried out at the same time as the dispensation application process at the Religious Court, while the recording is carried out after the dispensation decision. The second pattern is that the marriage is conducted after the decision of the marriage dispensation order while the registration is conducted at the same time. The third pattern is that both the marriage and the registration are carried out after a marriage dispensation decision that has permanent legal force.